The rewards of restraint in the collective regulation of foraging by harvester ant colonies - Gordon, Deborah M. (Nature (London), 2013)
Desert harvester ant colonies regulate their foraging activity and this collective behaviour appears to be under selection; colonies that forage less when conditions are poor have greater reproductive success, and the regulation of foraging behaviour appears to be inherited from parent to offspring colonies. 'Super' ants acting as one Ant colonies are sometimes thought of as superorganisms, implying that they are subject to natural selection at a colony level. In a long-term (27-year) study of the association between collective behaviour and reproductive success in colonies of the red harvester ant, Pogonomyrmex barbatus , Deborah Gordon has found that, yes, they can show this superorganism characteristic. In times of drought, harvester ants tend not to forage as much as they do in times of plenty; they seem to bide their time until circumstances improve. This trait of restraint is passed on to daughter colonies, showing that it can indeed be regarded as a colony-level trait. Collective behaviour, arising from local interactions 1 , allows groups to respond to changing conditions. Long-term studies have shown that the traits of individual mammals and birds are associated with their reproductive success 2 , 3 , 4 , 5 , 6 , but little is known about the evolutionary ecology of collective behaviour in natural populations. An ant colony operates without central control, regulating its activity through a network of local interactions 7 . This work shows that variation among harvester ant ( Pogonomyrmex barbatus ) colonies in collective response to changing conditions 8 is related to variation in colony lifetime reproductive success in the production of offspring colonies. Desiccation costs are high for harvester ants foraging in the desert 9 , 10 . More successful colonies tend to forage less when conditions are dry, and show relatively stable foraging activity when conditions are more humid. Restraint from foraging does not compromise a colony’s long-term survival; colonies that fail to forage at all on many days survive as long, over the colony’s 20–30-year lifespan, as those that forage more regularly. Sensitivity to conditions in which to reduce foraging activity may be transmissible from parent to offspring colony. These results indicate that natural selection is shaping the collective behaviour that regulates foraging activity, and that the selection pressure, related to climate, may grow stronger if the current drought in their habitat persists.